2003
DOI: 10.1046/j.1432-1033.2003.03701.x
|View full text |Cite
|
Sign up to set email alerts
|

Weak organic acid stress inhibits aromatic amino acid uptake by yeast, causing a strong influence of amino acid auxotrophies on the phenotypes of membrane transporter mutants

Abstract: The ability of yeasts to grow in the presence of weak organic acid preservatives is an important cause of food spoilage. Many of the determinants of acetate resistance in Saccharomyces cerevisiae differ from the determinants of resistance to the more lipophilic sorbate and benzoate. Interestingly, we show in this study that hypersensitivity to both acetate and sorbate results when the cells have auxotrophic requirements for aromatic amino acids. In tryptophan biosynthetic pathway mutants, this weak acid hypers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 22 publications
4
99
0
1
Order By: Relevance
“…Several years ago it was reported that previous experiments, in which Pdr12p has been identified as the main system responsible for AA extrusion from yeast cells, were experimental artifacts. 21 Authors observed inability of the mutant lacking Pdr12p to grow in the presence of acetate only for yeast auxotrophic for tryptophan and concluded that WOAs inhibited uptake of tryptophan from the medium. 21 It should be noted that all strains used in this study, parental and isogenic derivatives, are trp1-1 auxotrophs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several years ago it was reported that previous experiments, in which Pdr12p has been identified as the main system responsible for AA extrusion from yeast cells, were experimental artifacts. 21 Authors observed inability of the mutant lacking Pdr12p to grow in the presence of acetate only for yeast auxotrophic for tryptophan and concluded that WOAs inhibited uptake of tryptophan from the medium. 21 It should be noted that all strains used in this study, parental and isogenic derivatives, are trp1-1 auxotrophs.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reach maximum penetration of acids into cells, the pH values of YPD medium was adjusted to 3.0 with HCl. 21,29 Control cells were incubated in YPD medium at pH 6.75 or 3.0 without organic acids. At рН 3.0-4.5, YPD medium has been shown to act as a buffer system and recommended to be used for yeast incubation under WOA-induced stress.…”
Section: Yeast Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,25,37] Side-byside comparisons of the effects of acetic and sorbic acids (acids of identical pKa) show that it requires quite high acetic acid level (80-150 mM) in order to inhibit pH 4.5 cultures of glucose-repressed S. cerevisiae, whereas only 1-3 mM of the more liposoluble sorbic acid achieves the same degree of growth inhibition. [1,19,36] Therefore, while acetic acid may largely inhibit cells by generating a high intracellular pool of acetate anion and the lowering of intracellular pH (Figure 1b), the cytostatic effects of sorbic acid are suggested to be mainly due to its disordering of membrane structure. [2,36] High acetic acid is a potent inducer of yeast apoptosis; [6,[14][15][16] whereas the noted actions of benzoic and sorbic acids include a severe energy (ATP pool) depletion, [26] an inhibition of membrane trafficking, resulting in the arrest of macroautophagy [8] and, in the presence of oxygen, severe oxidative stress due to elevated endogenous production of reactive oxygen species (ROS) by a dysfunctional mitochondrial respiratory chain.…”
Section: A Brief Overview Of the Physiological Actions Of The Monocarmentioning
confidence: 99%
“…Resistances are induced to Acetic, but not propionic, sorbic or benzoic acids [19] Propionic, sorbic, benzoic acids, but not acetic acid [1,7] Key induced signalling pathway and activity HOG pathway signalling, leading to Hog1p MAP kinase activation [19] No evidence for a signalling pathway involvement; acid anion may act directly on the War1p transcription factor [13] Key action/target of the induced activity needed for the acquisition of resistance Phosphorylation of Fps1p, leading to Fps1p endocytosis [20] PDR12 gene induction, leading to an elevated plasma membrane level and activity of the Pdr12p ABC transporter [23,28] Probable related stress response Hog1p-directed downregulation of metalloid entry through the Fps1p channel [40] War1p activation in media containing leucine, methionine or phenylalanine as sole nitrogen source [9] Normal physiological function of the major target of the response Fps1p is the major glycerol channel of the plasma membrane, important for osmoadaptation [10,22,38] Pdr12p is also involved in export of the potentially toxic aromatic and branched-chain organic acids produced during amino acid catabolism [9] (2), a MAP kinase constitutively bound to, and that directly phosphorylates, Fps1p (3). This phosphorylation provides the signal for Fps1p endocytosis and degradation, eliminating this source of the acetic acid entry to the cell.…”
Section: Response To Inhibitory Acetic Acid Inhibitory Propionic Sormentioning
confidence: 99%